EXPLORING STAKEHOLDER VOICES: ISAK 35 IMPLEMENTATION ON FINANCIAL STATEMENTS IN ISLAMIC BOARDING SCHOOLS OF LEBAK REGENCY - Taufik Akbar; Lawe Anasta; Gugun Nugraha (PT. Altin Riset Publishing, 2025)
This study aims to explore the implementation of Interpretation of Financial Accounting Standards (ISAK) 35 in Islamic boarding schools (pesantren), focusing on Pondok Pesantren Daarus Sunnah Rangkasbitung, Lebak Regency, Banten Province. Although ISAK 35 is designed to enhance transparency and accountability in non-profit financial reporting, its implementation in pesantren still faces various obstacles. This study employs a qualitative approach using case study methods through in-depth interviews with six key stakeholders: pesantren administrators, supervisors, principals, finance staff, members of the Indonesian Ulema Council (MUI), and Muslim scholars. The findings reveal three main factors hindering ISAK 35 implementation: (1) inadequate accounting competence, (2) low understanding of financial reporting preparation, and (3) insufficient socialization and information. Stakeholders recognize the importance of accountability but emphasize alignment with pesantren values. Practical solutions proposed include: continuous training and mentoring, structured SOP development, accounting technology utilization, and effective socialization and advocacy. This study contributes to developing an adaptive and responsive ISAK 35 implementation model that respects the unique ecosystem of pesantren.